The Influence of the TikTok Poison Phenomenon as a Glow Up Trend on Interest in Buying Beauty Products - Hidayah, Isti Nurul; Setiowati, Dwi Agus Sulis; Sianipar, Dwina Elvrida Estefani; Anisa, Najwa (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2023)
The lifestyle offered by information changes new patterns in the behavior of human life to suit the times. This occurs in buying interest in a product which is influenced by many factors such as the glow up trend. One of them is the TikTok poison phenomenon, this has resulted in an increase in one's buying interest in beauty products as seen in the TikTok poison phenomenon. The purpose of this study was to find out whether the TikTok toxic phenomenon as a glow up trend has an influence on buying interest in beauty products. The population in this study were female students of the Faculty of Communication and Multimedia, Mercu Buana University, Yogyakarta, class of 2021. The sample was female students who used the TikTok app and had bought beauty products. The instrument used in this research is the ticktock poison phenomenon questionnaire as a glow up trend and buying interest. The data obtained were then analyzed using the Statistical Package for Social Science (SPSS). The results of this study state that the phenomenon of TikTok poisoning has a relationship with the buying interest of female students, where a Pearson Correlation value of 0.410 is obtained, which means that there is a strong relationship between the variable of the TikTok toxic phenomenon and the buying interest of female students. In addition, it was also shown that the TikTok poison phenomenon affected female students' buying interest by 16.8%. So that the other 83.2% is influenced by other variables not examined.